Adaptive Fault–Tolerant Position Control of a Hexacopter Subject to an Unknown Motor Failure - Falconì, Guillermo P.; Angelov, Jorg; Holzapfel, Florian (International journal of applied mathematics and computer science, 2018)
This paper presents a fault tolerant position tracking controller for a hexarotor system. The proposed controller has a cascaded structure composed of a position and an attitude control loop. The nominal controller is augmented by an adaptive control allocation which compensates for faults and failures within the propulsion system without reconfiguration of the controller. Simultaneously, it is able to implement a degraded control strategy which prioritizes specific control directions in the case of extreme degradation. The main contribution is a controller that is a step closer to application scenarios by including outdoor GPS-based flight tests, onboard computation and the handling of unknown degradation and failure of any rotor.